Pengaruh Earnings Per Share (EPS) Dan Pertumbuhan Penjualan Terhadap Harga Saham Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Nurul Marlina Putri; Elin Erlina Sasanti (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the effect of earnings per share (EPS) and sales growth on stock prices in food and beverage companies listed on the Indonesia Stock Exchange during the 2020-2023 period. This study uses a quantitative approach with secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange. The sampling technique used purposive sampling with a total sample of 32 companies and 128 observations. The data analysis technique used multiple linear regression analysis with the assistance of EViews 12 software. The results show that earnings per share has a positive and significant effect on stock prices, while sales growth has no significant effect on stock prices. These findings indicate that investors pay more attention to the company's ability to generate profits than sales growth in making investment decisions.